2007
DOI: 10.1177/0885328207077632
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Poly(lactide-co-glycolide) (PLGA)/ Nano-Hydroxyapatite (NHA) Scaffolds by Thermally Induced Phase Separation and Rabbit MSCs Culture on Scaffolds

Abstract: Biodegradable polymer/bioceramic composites scaffold can overcome the limitation of conventional ceramic bone substitutes such as brittleness and difficulty in shaping. To better mimic the mineral component and the microstructure of natural bone, novel nano-hydroxyapatite (NHA)/polymer composite scaffolds with high porosity and well-controlled pore architectures as well as high exposure of the bioactive ceramics to the scaffold surface is developed for efficient bone tissue engineering. In this article, regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(72 citation statements)
references
References 40 publications
3
69
0
Order By: Relevance
“…For example, adhesion, proliferation and differentiation of mesenchymal stem cells were studied on nano-sized HA/polyamide biocomposite scaffolds. The results indicated that such biocomposites exhibited a good biocompatibility and an extensive osteoconductivity with host bone in vitro and in vivo and proved that nano-sized HA/polyamide scaffolds had a potential to be used in orthopedic, reconstructive and maxillofacial surgery [664][665][666].…”
Section: Nanodimensional and Nanocrystalline Calcium Orthophosphates mentioning
confidence: 86%
“…For example, adhesion, proliferation and differentiation of mesenchymal stem cells were studied on nano-sized HA/polyamide biocomposite scaffolds. The results indicated that such biocomposites exhibited a good biocompatibility and an extensive osteoconductivity with host bone in vitro and in vivo and proved that nano-sized HA/polyamide scaffolds had a potential to be used in orthopedic, reconstructive and maxillofacial surgery [664][665][666].…”
Section: Nanodimensional and Nanocrystalline Calcium Orthophosphates mentioning
confidence: 86%
“…Further, nano-hydroxyapatite-PLGA scaffolds support greater rabbit mesenchymal stem cell (MSC) growth and alkaline phosphatase activity than PLGA scaffolds. 12 The addition of nanohydroxyapatite particles into the PLGA scaffold confers better biological, mechanical, and degradation properties.…”
Section: Nanomaterials For Bone Regenerationmentioning
confidence: 99%
“…For example, hydroxyapatite/PLGA composites possess the osteoconductive properties of hydroxyapatite and biodegradability of PLGA [91]. Polycaprolactone-tricalcium phosphate (PCL-TCP) scaffolds combined with recombinant human BMP7…”
Section: Metallic and Composite Scaffoldsmentioning
confidence: 99%